2011
DOI: 10.1002/cncr.26439
|View full text |Cite
|
Sign up to set email alerts
|

Effect of metformin on survival outcomes in diabetic patients with triple receptor‐negative breast cancer

Abstract: Background Recent observational studies have shown that metformin use in diabetics decreases both cancer incidence and mortality. Metformin use is also independently predictive of pathologic complete response. We explored the association between metformin use and survival outcomes in patients with triple receptor-negative breast cancer (TNBC) receiving adjuvant chemotherapy. Methods The Breast Cancer Management System database of The University of Texas M.D. Anderson Cancer Center identified 1448 women who r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
148
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(155 citation statements)
references
References 58 publications
3
148
0
4
Order By: Relevance
“…A similar, also historical, series of epithelial ovarian cancer has demonstrated clinical benefit with increased progression-free survival and overall survival in diabetics taking metformin and receiving taxane/carboplatin chemotherapy compared with nondiabetics or diabetics not on metformin (68). However, incidental metformin use has not demonstrated survival benefit in two case series of diabetics with breast cancer (5,67). This concept of combining metformin with neoadjuvant chemotherapy is in prospective trials of metformin alongside paclitaxel and FAC; docetaxel, epirubicin, and cyclophosphamide AE metformin; and in ISPY2 (ganitumab þ metformin).…”
Section: Metformin and Breast Cancer Trialsmentioning
confidence: 96%
“…A similar, also historical, series of epithelial ovarian cancer has demonstrated clinical benefit with increased progression-free survival and overall survival in diabetics taking metformin and receiving taxane/carboplatin chemotherapy compared with nondiabetics or diabetics not on metformin (68). However, incidental metformin use has not demonstrated survival benefit in two case series of diabetics with breast cancer (5,67). This concept of combining metformin with neoadjuvant chemotherapy is in prospective trials of metformin alongside paclitaxel and FAC; docetaxel, epirubicin, and cyclophosphamide AE metformin; and in ISPY2 (ganitumab þ metformin).…”
Section: Metformin and Breast Cancer Trialsmentioning
confidence: 96%
“…30-35 ) associated with metformin exposure must be balanced against others that do not show such associations (e.g., refs. [36][37][38][39]. Some studies suggest unexpected variables that might modify the effects of metformin, including pharmacoepidemiologic evidence that exposure to both a statin drug and metformin is necessary for an important antineoplastic effect to be observed ( 40 ) and laboratory evidence that administration of proton pump inhibitors limits cellular uptake of metformin ( 41 ).…”
Section: Pharmacoepidemiology: Hypothesis-generating Cluesmentioning
confidence: 99%
“…Some pharmacoepidemiologic studies have suggested that metformin may have antineoplastic activity (21)(22)(23)(24)(25)(26)(27) but others have not supported this view (28)(29)(30)(31). Similarly, some (10) but not all (32) laboratory studies suggest that metformin has antineoplastic activity.…”
Section: Introductionmentioning
confidence: 99%